Meningkatkan Kemampuan Dasar Kognitif Melalui Permainan “Rainbowling” Pada Anak Kelompok B-1 Tk Islam Al Falah Kecamatan Pesantren Kota Kediri - Suwarti, Suwarti (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2018)
Based on the observation on the development activities of the children of B-1 Islamic Al-Falah group of Pesantren Sub-district of Kediri City, found the low information about the children's sports, especially the sport of bowling, and lack of enthusiasm and enthusiasm in teaching and learning activities possibly caused by less attractive and tend to be passive for children. Accordingly, an interesting, effective, and fun learning strategy is needed to develop the child's cognitive basic skills. Through the game, Rainbowling is expected to develop the child's cognitive basic skills easily and the child does not feel bored. The form of action that will be done is through the game "Rainbowling" can develop the basic cognitive abilities in the students because through this game the child does not feel bored and give children the opportunity to be active. Based on the background, this writing was conducted with the aim of knowing that through the game "Rainbowling" can improve the cognitive basic skills in children group B-1 Islamic Kindergarten Al-Falah Kecamatan Pesantren Kediri. The subjects in this study were students of the B-1 TK Islam Al-Falah group of Pesantrens of the academic year 2015-2016 addressed on Jl. Brigjend.Pol. Imam Bachri No.123 Kota Kediri, with 21 children consisting of 7 girls and 14 boys. These students become targets and as well as a source of research data. Based on the above data, the basic cognitive abilities of students have improved. This is evident from the percentage of mastery of cognitive basic skills in pratindakan and in the first cycle that only reached 66.7%. Then the basic cognitive abilities of students experience an increase in the second cycle of 85.7%. Based on the results of research and discussion can be concluded that through the game Rainbowling can develop the basic cognitive abilities of students B-1 TK Islam Al-Falah School of Pesantren Kediri School Year 2015/2016. In addition, the interest of children to understand the concept of arithmetic is increasing after done with game Rainbowling Game.